2021
DOI: 10.1038/s41467-021-26366-w
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis of soluble membrane attack complex packaging for clearance

Abstract: Unregulated complement activation causes inflammatory and immunological pathologies with consequences for human disease. To prevent bystander damage during an immune response, extracellular chaperones (clusterin and vitronectin) capture and clear soluble precursors to the membrane attack complex (sMAC). However, how these chaperones block further polymerization of MAC and prevent the complex from binding target membranes remains unclear. Here, we address that question by combining cryo electron microscopy (cry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 66 publications
7
31
0
Order By: Relevance
“…sMAC is believed to consist of C5b-7, C8, multiple copies of C9, and several copies of Vn and Clu ( Barnum et al, 2020 ; Preissner et al, 1989 ). This was recently supported by Menny et al, 2021 , who revealed that sMAC generated by zymosan particles in serum contains at least one to three copies of C9. Our data suggest that sMAC generated by bacteria is present in similar stoichiometries, but on average, contains less C9 molecules, especially for sMAC generated by MAC-resistant E. coli ( Figures 6 and 7 ).…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…sMAC is believed to consist of C5b-7, C8, multiple copies of C9, and several copies of Vn and Clu ( Barnum et al, 2020 ; Preissner et al, 1989 ). This was recently supported by Menny et al, 2021 , who revealed that sMAC generated by zymosan particles in serum contains at least one to three copies of C9. Our data suggest that sMAC generated by bacteria is present in similar stoichiometries, but on average, contains less C9 molecules, especially for sMAC generated by MAC-resistant E. coli ( Figures 6 and 7 ).…”
Section: Discussionmentioning
confidence: 71%
“… Menny et al, 2021 recently reported that the commercially available sMAC used in our study consists of C5b-8, one to three copies of C9 and several copies of Vn and Clu, using proteomics, cross-linking MS, and cryo-electron microscopy. Here, we compared the average composition of sMAC generated by MAC-resistant E. coli with commercial sMAC by profiling sMAC components with liquid chromatography-tandem mass spectrometry (LC-MS/MS).…”
Section: Resultsmentioning
confidence: 99%
“…[38] In addition to its chaperone capacity, Clusterin functions in sperm maturation, [39] cell differentiation, [40] regulation of cell death and survival mechanisms, [41] and as an anti-inflammatory inhibitor of the complement system. [42,43] Moreover, it is often overlooked that Clusterin is an apolipoprotein (ApoJ) that has been identified in plasma high-density lipoprotein particles, suggesting a role in lipid and cholesterol metabolism. [44] Indeed, together with ApoE, Clusterin is one of the major apolipoproteins in the brain parenchyma, but its role in lipid metabolism in the central nervous system (CNS) is not well understood.…”
Section: Clusterin An Unusual Chaperonementioning
confidence: 99%
“…[137] Clusterin exerts anti-inflammatory effects mainly by suppressing complement activation. [42,43] Because synapse pruning by astrocytes and microglia during development involves the complement system, [138] upregulation of complement proteins in AD has been associated with synapse loss and cognitive decline. [139] Accordingly, inhibition of the complement system by Clusterin may be neuroprotective.…”
Section: Function Of Clusterin In Neuroinflammationmentioning
confidence: 99%
“…Recent structural studies of the MAC and its components have provided insight into the final assembled architecture and the structural rearrangements that enable its assembly, such as the canonical unravelling of the transmembrane β-hairpins within the MACPF/CDC domain and global shifts of its ancillary domains (20). These studies and others indicate that large scale conformational rearrangements, such as movement of TMH1 in C9, are characteristic of MAC assembly (21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%